Pancreatitis: critical care update. Issue 2 (February 2021) - Taylor, Ashleigh; Docking, Robert
Abstract: Severe acute pancreatitis (SAP) is a common pathology requiring critical care input. Patients often present with evidence of physiological dysfunction that may require organ support for optimization. Various scoring systems are available which can help in identifying those most at risk of morbidity and mortality. Complications can be significant, and may require surgical intervention for management. As such these patients should be managed with full multidisciplinary input to ensure appropriate targeted treatment. Underlying causes for SAP should be aggressively investigated to reduce the potential for recurrent episodes and where appropriate allow for secondary preventative measures. These patients often require prolonged and recurrent intensive care stays. Of those who are discharged, ongoing issues with chronic pain and nutrition are not uncommon and can lead to significant psycho-social challenges in the community.